2015
DOI: 10.1007/s12639-015-0676-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo anthelmintic activity of seed extract of Coriandrum sativum compared to Niclosamid against Hymenolepis nana infection

Abstract: Phytotherapy can be an alternative for the control of gastrointestinal parasites in human and animals. Coriander (Coriandrum sativum L.) is a medicinal plant which grown as a spice crop all over the world. The seeds of this plant have been used to treat parasitic disease, indigestion, diabetes, rheumatism and pain in the joints. This study was carried out to compare the efficacy of Niclosamid and alcoholic seed extract of C. sativum on Hymenolepis nana infection, in vivo and vitro. For in vivo study, Balb/c mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…Ethanol extract of coriander seeds could destroy adult tapeworm, Hymenolepis nana . This effect was increased dose‐dependently as higher doses could eliminate the worm in a shorter period of time (Hosseinzadeh et al., 2016).…”
Section: Pharmacological Aspectsmentioning
confidence: 99%
“…Ethanol extract of coriander seeds could destroy adult tapeworm, Hymenolepis nana . This effect was increased dose‐dependently as higher doses could eliminate the worm in a shorter period of time (Hosseinzadeh et al., 2016).…”
Section: Pharmacological Aspectsmentioning
confidence: 99%
“…contortus and related gastrointestinal nematodes (GIN) of small ruminants are the most widely investigated organisms in in vivo models, whereas sheep and goats are the major animals in which such clinical investigations have been reported [86,87,111,112]. Tere are few reports involving trials in pigs, chickens, goldfsh, snails, rats, and mice [113][114][115][116][117]. Te ability of test substances to reduce faecal egg count (FEC), a typical measure of efects on fecundity, and postmortem intestinal worm burden are the parameters measured in in vivo assays.…”
Section: General Overview Of Anthelmintic Evaluation Of African Medic...mentioning
confidence: 99%
“…Anticolitis: hydroalcoholic seed extract (250-1,000 mg/kg PO) and essential oil (0.25-1 ml/kg PO) significantly and dosedependently protected rats from acetic acid-induced colitis (Heidari et al, 2016). Anthelminthic: in vitro and in vivo studies showed moderate effects of aqueous and alcoholic extracts against Haemonchus contortus and Hymenolepis nana (Eguale et al, 2007;Hosseinzadeh et al, 2016). Analgesic and antiinflammatory: few studies showed moderate effects of aqueous and ethanolic (50-200 mg/kg PO) seed extracts in different rodent models, as reviewed (Laribi et al, 2015).…”
Section: Likely Safe and Effective D34mentioning
confidence: 99%